1981
DOI: 10.1172/jci110164
|View full text |Cite
|
Sign up to set email alerts
|

Impaired growth hormone secretion in the adult population: relation to age and adiposity.

Abstract: A B S T R A C T Growth hormone (GH) release was studied in adults of normal stature, ages 21-86 yr. The subjects were 85-115% of ideal body weight, between the 5th and 95th percentiles in height, and free ofactive or progressive disease. 9 to 12 individuals in each decade from third to ninth were evaluated. The following criteria of GH status were measured: serum GH concentration, analyzed by radioimmunoassay at halfhour intervals for 4 h after onset of sleep, and at 1-h intervals from 8 a.m. to 4 p.m. in 52 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
290
2
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(326 citation statements)
references
References 52 publications
32
290
2
2
Order By: Relevance
“…First, consistent with our previous study of resistance-trained older people, it appears that habitual endurance exercise does not ameliorate the age-related decline in circulating IGF-I or its most abundant binding protein, in one estimate of IGF-I bioavailability, the calculated ratio of IGF to IGFBP-3, or, by inference, the decline in GH secretion. With regard to the latter inference, although we did not measure GH in this study, previous work from our laboratory and from others clearly shows that healthy older men uniformly show decreased GH secretory capacity, either spontaneously or in response to provocative stimuli such as exercise (1)(2)(3)(4), and that even an intense and sustained program of exercise training did not restore these deficits (11). The second major finding of this study was that our group of very active older men showed striking increases in circulating SHBG, sufficient to misrepresent calculated estimates of bioavailable testosterone.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…First, consistent with our previous study of resistance-trained older people, it appears that habitual endurance exercise does not ameliorate the age-related decline in circulating IGF-I or its most abundant binding protein, in one estimate of IGF-I bioavailability, the calculated ratio of IGF to IGFBP-3, or, by inference, the decline in GH secretion. With regard to the latter inference, although we did not measure GH in this study, previous work from our laboratory and from others clearly shows that healthy older men uniformly show decreased GH secretory capacity, either spontaneously or in response to provocative stimuli such as exercise (1)(2)(3)(4), and that even an intense and sustained program of exercise training did not restore these deficits (11). The second major finding of this study was that our group of very active older men showed striking increases in circulating SHBG, sufficient to misrepresent calculated estimates of bioavailable testosterone.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, in a study of young adults, Weltman et al (32) demonstrated an inverse relationship between fat mass and IGF-I concentration. Others that examined the same parameters in young and older men did not report subgroup analyses in the same age range as our participants (1,33). The absence of a correlation between IGF-I and percent body fat in older men that we have demonstrated is consistent with the age-related, exerciseindependent suppression of GH/IGF-I that we observed: that is, age per se appears to exert a more potent effect on GH/IGF-I secretion than does adiposity.…”
Section: European Journal Of Endocrinology (1998) 138mentioning
confidence: 94%
See 1 more Smart Citation
“…In recent work in which we have used RNase protection to distinguish and quantify the expression of different muscle IGF-1 isoforms we have found that both the autocrine (MGF) and the systemic type (muscle L.IGF-1) that is also produced by the muscle are both markedly upregulated by stretch and stretch combined with stimulation (McKoy et al 1999). During ageing, however, the circulating growth hormone and IGF-1 are known to decrease markedly particularly after the initial growth spurt (Rudman et al 1981). Although IGF-1s produced via growth hormone stimulation are important during early postnatal muscle development, it appears that IGF-1 produced by muscle during exercise becomes more important for the maintenance of muscle mass.…”
Section:        mentioning
confidence: 99%
“…The concentration of IGF-I had been known to be influenced by age [1][2][3][4][5][6]. However, there was no reference value for serum IGF-I in adults based on the extraction method, except in a recent Swedish report [7].…”
mentioning
confidence: 99%